2021
DOI: 10.1096/fba.2021-00046
|View full text |Cite
|
Sign up to set email alerts
|

Nerve density in cancer: Less is better

Abstract: The density of nerves in cancer is emerging as a relevant clinical parameter for patient survival.Nerves in the tumor microenvironment have been associated with poor survival and recurrence, particularly if involved in perineural invasion. However, usually only a few nerves inside a tumor are affected by perineural invasion, while most nerves are not. Mechanistic studies have shown nervesecreted factors promote tumor growth and invasion thereby making tumors more aggressive.Therefore, the overall number of ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
(243 reference statements)
0
11
0
Order By: Relevance
“…Requires further standardization H&E IHC: Pan-cytokeratin for epithelium, S100 or TUJ1 for nerve. [49,79] H&E: hematoxylin and eosin. IHC: immunohistochemistry phenotypes that have been associated with adverse outcomes, it is time to develop a comprehensive set of neural parameters that can be used to facilitate treatment selection and predict response to treatment of oral cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Requires further standardization H&E IHC: Pan-cytokeratin for epithelium, S100 or TUJ1 for nerve. [49,79] H&E: hematoxylin and eosin. IHC: immunohistochemistry phenotypes that have been associated with adverse outcomes, it is time to develop a comprehensive set of neural parameters that can be used to facilitate treatment selection and predict response to treatment of oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve fibers are quantified to determine nerve density due to axonogenesis and neurogenesis whereas nerve trunks or fascicles are quantified to assess nerve density due to neurotropism. [79] Factors secreted by nerves, including neurotransmitters, chemokines, neuropeptides, and neurotrophins, enhance neurite growth and cancer progression. In OSCC, the neuropeptide galanin enhances neurite outgrowth as well as growth, invasion, and metastasis of cancer cells.…”
Section: Nerve Densitymentioning
confidence: 99%
“…[25] In solid tumors, studies from tumors that are developed from highly innervated organs such as pancreatic, head and neck, prostate, and colorectal cancer have shown that nerve density and neurotropism are associated with increased metastasis, morbidity, and mortality. [26][27][28][29] These findings of the impact of nerve density in patient's outcome have led to study different mechanisms of interaction among nerve fibers, tumor cells, and TME.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…[1,76] The implications of the interactions among immune cells and nerve fibers are highlighted by the fact that tumor-associated nerve fiber density is associated to patient's prognosis in several solid tumors. [29] Immune cell and nerve fiber interaction drives physiological processes related to tissue protection, this phenomenon is a key factor for immune-regulation, and has being explained by the presence of functional interrelated paths between the NS and the immune system known as "neuroimmune cell units" (NICUs). In NICUs, immune cells and neuronal cells can colocalize and interact in many tissues around the body playing a significant role in many physiological processes such as tissue repair, inflammation, cancer progression, and especially in immune modulation of T-cells, macrophages, natural killers, and dendritic cells, among others.…”
Section: Interaction Between Nerves and Immune Cellsmentioning
confidence: 99%
“…Determining the outcome of the tumor at the time of diagnosis is increasingly important for treatment choice and patient segmentation, and as nerve infiltration in the tumor microenvironment is associated with tumor aggressiveness 31,58,59,76 , the assessment of nerve density may become part of routine clinicopathological analyses in oncology, as well as increasing utility through imaging, particularly in prostate cancer 77 . Similarly, neurotrophic growth factors and their receptors are overexpressed in human tumors 78,79,80,81 and they could also be of value in cancer clinicopathology.…”
Section: -Conclusion: Emerging Clinical Translationmentioning
confidence: 99%